2006
DOI: 10.1002/iroh.200610913
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Diversity in Chronically versus Episodically Acidified Adirondack Streams

Abstract: The relationship between algal species richness and diversity, and pH is controversial. Furthermore, it is still unknown how episodic stream acidification following atmospheric deposition affects species richness and diversity. Here we analyzed water chemistry and diatom epiphyton dynamics and showed their contrasting behavior in chronically vs. episodically acidic streams in the Adirondack region. Species richness and diversity were significantly higher in the chronically acidic brown water stream, where orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The weaker prediction of diatoms compared to those of macroinvertebrate and fish populations in upslope ungaged watersheds suggests that aquatic biota more strongly influenced by episodic changes in water sources (i.e., groundwater vs. surface water) are more difficult to predict with our model. This finding is consistent with evidence that water chemistry during runoff events has greater influence on diatom species richness and diversity than water chemistry during baseflow (Passy et al 2006, Burns et al 2008. Almost certainly there are some dynamic characteristics of RR, such as antecedent conditions and rainfall intensity, that are not included in the simple regression model that only applied 20 storms during 1991-1993.…”
Section: Discussionsupporting
confidence: 82%
“…The weaker prediction of diatoms compared to those of macroinvertebrate and fish populations in upslope ungaged watersheds suggests that aquatic biota more strongly influenced by episodic changes in water sources (i.e., groundwater vs. surface water) are more difficult to predict with our model. This finding is consistent with evidence that water chemistry during runoff events has greater influence on diatom species richness and diversity than water chemistry during baseflow (Passy et al 2006, Burns et al 2008. Almost certainly there are some dynamic characteristics of RR, such as antecedent conditions and rainfall intensity, that are not included in the simple regression model that only applied 20 storms during 1991-1993.…”
Section: Discussionsupporting
confidence: 82%
“…Acidification episodes timed with sensitive life stages can result in the elimination of an annual age class (McComick and Leino, 1999). Taxonomic richness of macroinvertebrate communities was also found to be lower in episodically acidified streams than in streams with similar base‐flow chemistry that did not episodically acidify (Lepori et al, 2003), and diversity of diatom communities was found to be lower in an episodically acidified stream than a neighboring stream that was chronically acidified (Passy et al, 2006). Assessing the extent of acidic deposition effects on stream ecosystems therefore requires that the variability of stream chemistry be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that improvements in pH and Al can occur at high flow, in the absence of trends for lower flow conditions in the most acid sensitive watershed, has consequences for the assessment of biological recovery. Both chronic and episodic acidification have been shown to have negative impacts on aquatic biota, including fish (Baker et al, ), macroinvertebrates (Lepori & Ormerod, ), and diatoms (Passy, Ciugulea, & Lawrence, ), yet aquatic health assessments consistently use the more widely available trends in chronic streamwater chemistry, which cannot always adequately explain changes in biological indicators. For example, in SHEN, improvements in brook trout abundance at the most acidic sites (including Paine Run) did not match the chronic stream chemical trends at those sites (Jastram, Snyder, Hitt, & Rice, ).…”
Section: Summary and Implicationsmentioning
confidence: 99%